A 2–12 GHz power distributed amplifier for broadband localization- and sensor systems based on PN-sequences - Sewiolo, Benjamin; Weigel, Robert (IEEE International Conference on Ultra-Wideband, 2008, 2008)
In this paper the analysis, design and measurement of a 2-12 GHz power distributed amplifier for ultra-wideband localization- and sensor applications is presented. The circuit integrates four cascode gain cells, which are capacitively coupled to the base line for power optimization. The collector line has been tapered for efficiency improvement. More than 14 dBm have been measured in the desired frequency range with an associated gain of 9 dB and a gain flatness of plusmn0.5 dB with total power consumption of 250 mW. To the authors knowledge, this is the highest output power achieved by a distributed amplifier in SiGe technology in this frequency range. The chip size of the compact amplifier is 1.16 mm2 and has been fabricated in a low-cost 0.25 mum SiGe BiCMOS technology with a transit frequency of 25 GHz. Good agreement between simulation and measurement were achieved.
elib2cris::1512001600,sewiolo2008b